Techno-Socio-Economic Assessment Of Farmers Practices In Rice Cultivation In Thiruvananthapuram District - Manoj S (Department of Agricultural extension, College of Agriculture, 2000)
In developing countries existing research systems are not always able to generate technologies needed to solve the problems of resource poor farmers. Such farmers are forced to develop their own technologies suited for particular conditions. So farmers’ practices and farmer experimentations have got growing significance now a days. A research study was under taken to asses the socio-economic and technical aspects of farmers’ practices in rice cultivation in Thiruvananthapuram district. Farmers practices included all those practices which were actually followed by farmers in the rice cultivation consisting indigenous and recommended practices. The experimental area selected was Andoorkonam Ela of Kaniyapuram village panchayat. The study was conducted in three phases. Phase-1 consisted of collecting data regarding the profile characteristics of rice farmers. During Phase-II, all farmers’ practices were collected using non-participant observation technique. The third phase consisted of techno-socio-economic assessment and assessing the ecofriendliness of farmers’ practices. For this study, two sets of respondents were taken- the practicing farmers and scientists/ extension officials. The research endeavour identified 51 farmers’ practices in rice cultivation. These practices were documented and described along with their scientific rationale. Majority of the farmers (54.29 per cent) were in the low knowledge group regarding the knowledge of farmers about the recommended practices. However, most of them (54.29 per cent) were in high adoption category regarding the adoption of farmers practices. • The variables education, annual income, exposure to information source, social participation, extension orientation, economic motivation, innovativeness risk preference and participation in PTD were having a positive and significant correlation with knowledge of rice farmers about the recommended practices. Adoption of farmers’ practices was influenced by the variables such as occupation, farming experience, total area under paddy, social participation, economic motivation and innovativeness. Soaking the seeds in water for 18-24 hours, using the variety PTB-9 for the second crop and preparing the main field using tractor were practices which showed cent per cent adoption. About ninety per cent of the farmers adopted the practice of sprinkling cowdung slurry over the soaked seeds. Application of poultry manure in place of FYM was adopted by more than fifty per cent of the rice farmers. The most ecofriendly practice as perceived by farmers was the sprinkling of cowdung slurry over soaked and heaped rice seeds in order to enhance germination. Using poultry manure in place of the costly and unavailable FYM was the most efficient farmers’ practice as rated by farmers and scientists/ extension officials. The other efficient farmers’ practices were the ‘plantain fruit bait for squirrels and mynas’ and bird scaring techniques such as ‘placing coconut leaflets, placing coloured plastic bags, bird scarers and stretching audio and video tapes over the field. A systematic and organised effort should be taken to document and assess these farmers’ practices throughout the state which is inevitable to improve efficiency and productivity in rice cultivation. A multi disciplinary approach is essential for such type of research and a comprehensive feed back should be given to the research system in Kerala.